2022
DOI: 10.1016/j.healthpol.2022.01.002
|View full text |Cite
|
Sign up to set email alerts
|

“My problems aren't severe enough to seek help”: Stress levels and use of mental health supports by Canadian hospital employees during the COVID-19 pandemic

Abstract: Due to the unique set of stressors associated with the COVID-19 pandemic, healthcare workers in acute care settings may be facing elevated rates of mental health symptomatology. The purpose of this study was to assess levels of depression, anxiety, and stress in a sample of healthcare employees working in hospitals and their use of formal and informal mental health supports. Data was gathered over a three-week period in December 2020 as COVID cases began to rise sharply in Ontario, Canada. Results from an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Several studies were conducted during the same period as this study. Ménard et al have shown that the prevalence of depression, anxiety and stress among Canadian HCWs was 14.4%, 21.8% and 13.5%, respectively 45. The lower prevalence in Canada might be explained by the difference in the healthcare systems.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies were conducted during the same period as this study. Ménard et al have shown that the prevalence of depression, anxiety and stress among Canadian HCWs was 14.4%, 21.8% and 13.5%, respectively 45. The lower prevalence in Canada might be explained by the difference in the healthcare systems.…”
Section: Discussionmentioning
confidence: 98%
“…Ménard et al have shown that the prevalence of depression, anxiety and stress among Canadian HCWs was 14.4%, 21.8% and 13.5%, respectively. 45 The lower prevalence in Canada might be explained by the difference in the healthcare systems. Different healthcare systems across countries can lead to differences in the prevalence of mental health problems among HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations should continue to evaluate how RNs are coping and adjusting to the ongoing pandemic now in its third year and throughout vaccine deployment on both sides of the border. Ongoing analysis of the experiences of other healthcare workers, similar to work done in the first wave by Ménard et al (2022 ) (e.g., physicians, allied health professionals, non-medical hospital staff), to gather quantitative data on stress and coping may also be warranted. Lastly, continued work should be done to evaluate the ongoing effect of the known Canadian ( Bourgeault, 2021 ) and global nursing shortage ( Nebehay, 2021 ) on healthcare in both countries .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a group approach would have been more adequate as it allows sharing needs and difficulties together. However, HCWs also reported to believe their problems were not severe enough to require these services and to be able to manage them on their own, despite the high psychological distress reported ( 39 42 ).…”
Section: Introductionmentioning
confidence: 99%